Analysis of Religious Characters and Logical Thinking Skills After Using Solar System Teaching Material Integrated with Islamic Science - Eka Yulida Fitriani; Fidia Fibriana (Yayasan Keluarga Guru Mandiri, 2020)
This study aims to analyze the religious character and logical thinking skills of students after using solar systems teaching materials integrated with Islamic Science. The type of research used is descriptive analysis with a Post-Test-Only with Non-equivalent Groups research design. The research data were obtained from observation sheets, questionnaire sheets, and posttest. The religious character and students’ logical thinking skills of the experiment class students are better than the control class. Students in the experiment class were superior to the control class. The effect of the correlation of the use of teaching materials on the religious character of the students obtained 79.21%, while the effect of the correlation of the use of teaching materials on students’ logical thinking skills was 38.44%. The study concludes that students’ religious character after using solar system teaching materials integrated Islamic science is dominant in the “very good” category and students’ logical thinking skills after the use of solar system teaching materials integrated Islamic science is dominant in the high category.